Forecast of optimal strategies for TPP under conditions of the uncertainty of the daily load schedule of Ukraine’s integrated power system - Bogoslavska O.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2012)
To solve the problem posed in this work, we analyze the methods of short-term forecast of the electric power load schedules for Ukraine’s integrated power system. Within any methods of forecast, it is impossible to avoid errors and to exactly predict a daily load schedule. This does not allow one, in turn, to exactly calculate the payment to the producers of the electric power supplied to state’s enterprise “Energorynok.” We describe a method guaranteeing the reception of payments by thermal power plants under conditions of the uncertainty of the forecasted electric power consumption schedule.We have developed a mathematic model of efficient price claims of power plants in the case of an unpredictable daily power load schedule. The model is constructed on the basis of the mathematic theory of games with the use of the Nash-Slater equilibrium. Model’s peculiarity consists in that each of the competitors is oriented to the possibility for the worst values of uncertainty to be realized. The final result of modeling is a minimally guaranteed amount of payment to each power plant.